New technologies, new hazards: Need for evidence base: A report on the health status and safety measures in a biotechnology factory in Bangalore - Sudhashree V; Lalitha K; Surendra VHH; Rohith K (Wolters Kluwer Medknow Publications, 2007)
Background: In highly competitive economies, the fast-paced development of new and improved products and services inevitably spurs the development of new technologies, of which one-fifth growth has been in the biotechnology sector. Advances in technologies provide opportunities to minimize the drudgery of work and to eliminate old hazards, but they may create new currently unrecognized risks to workers. Objectives: To assess the morbidity pattern among workers in the biotechnology industry and also to find out the health and safety measures provided to the workers. Materials and Methods: A cross-sectional study was conducted in a biotechnology industry in Bangalore, which covered 779 employees who underwent health examination and blood and urine investigations; of the 779 employees, 600 were permanent employees and 179 were contract employees. Results and Discussion: The common morbidity among the workers included refractory errors; allergic contact dermatitis; hypertension; abnormal pulmonary function tests (61, 10.2%), of which 23 (37.7%) were from the production department; high eosinophil count (110, 14.1%). Majority, i.e., 46 (41.8%) worked in the production department. The safety measures provided to the workers are adequate, but there is a need to insist on regular use of personal protective devices by newly employed and contract laborers.